Mechanical behaviour of timber‐to‐concrete connections with inclined screws - Kavaliauskas, Saulius; Kvedaras, Audronis Kazimieras; Valiūnas, Balys (Journal of Civil Engineering and Management, 2007)
The purpose of this paper is to adopt the Johansen’s yielding theory as a possibility to predict the ultimate load for timber‐to‐concrete joints using self‐tapping threaded connectors screwed at an angle into the wood. The ultimate load‐bearing capacity of a single connector is predicted to be when either the stresses in the wood reach the plastic failure stress level or when a combination of plastic failure in wood and dowel is attained. K. W. Johansen assumed that no axial tension occurred in the dowel and, thus no frictional contribution affected the lateral load‐bearing capacity. However, the joints with inclined fasteners are first affected by tension load, so the withdrawal capacity of the screws has to be taken into account. In order to determine the load bearing capacity for specific connector geometry, the kinematical possible failure modes are determined. The screw in the concrete part of connection was taken as rigidly embedded and thus no deformations appeared. The study showed that the load‐bearing capacity for connections with inclined high tensile strength screws can be predicted using the yielding theory, but this theory was unable to predict precisely the failure mode. Possible reasons for that include limited fastener ductility and influence of the screw inclination on the strength properties of timber. Medienos-betono jungčių su įžambiai įsriegtais medsraigčiais mechaninė elgsena Santrauka. Straipsnyje atlikta kompozitinių medienos ir betono jungčių skaičiavimo pagal Johanseno takumo teoriją analizė. Naudojantis vadinamosios Europos takumo teorijos (European Yielding Theory) pagrindais, užrašytos lygtys kompozitinei medienos-betono jungčiai su įžambiai į medieną įsriegtais medsraigčiais, atlikti tokių jungčių eksperimentiniai tyrimai ir nustatytos jų laikomosios galios reikšmės, kurios palygintos su teoriškai apskaičiuotomis. Reikšminiai žodžiai: medienos ir betono jungtis, įžambiai įsriegti medsraigčiai kaip jungės, takumo teorija. First Published Online: 14 Oct 2010